Roots and Trajectories of Violent Extremism and Terrorism: A Cooperative Program of the U.S. National Academy of Sciences and the Russian Academy of Sciences (1995-2020) - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
During the past 25 years, the U.S. National Academies of Sciences, Engineering, and Medicine, in collaboration with the Russian Academy of Sciences, have carried out a wide variety of activities to improve understanding of the challenges in containing and reducing ethnic conflicts, violent extremism, and terrorism. Roots and Trajectories of Violent Extremism and Terrorism provides an overview of this cross-ocean program, which has involved American and Russian scientists, engineers, and medical professionals from a large number of government agencies, leading research institutions, think tanks, educational institutions, analytical centers, and consulting and commercial firms in the two countries. This report highlights challenges addressed by the academies over many years that remain of current interest as the U.S., Russian, and other governments continue to cope with old and new forms of aggression that threaten the livelihood of populations at home and abroad.

Traumatic Brain Injury: A Roadmap for Accelerating Progress - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Every community is affected by traumatic brain injury (TBI). Causes as diverse as falls, sports injuries, vehicle collisions, domestic violence, and military incidents can result in injuries across a spectrum of severity and age groups. Just as the many causes of TBI and the people who experience it are diverse, so too are the physiological, cognitive, and behavioral changes that can occur following injury. The overall TBI ecosystem is not limited to healthcare and research, but includes the related systems that administer and finance healthcare, accredit care facilities, and provide regulatory approval and oversight of products and therapies. TBI also intersects with the wide range of community organizations and institutions in which people return to learning, work, and play, including the education system, work environments, professional and amateur sports associations, the criminal justice system, and others. Traumatic Brain Injury: A Roadmap for Accelerating Progress examines the current landscape of basic, translational, and clinical TBI research and identifies gaps and opportunities to accelerate research progress and improve care with a focus on the biological, psychological, sociological, and ecological impacts. This report calls not merely for improvement, but for a transformation of attitudes, understanding, investments, and care systems for TBI.

COVID-19, Health Equity, and the Asian American, Native Hawaiian, and Pacific Islander Communities: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Communities of color have been among the hardest hit by the COVID virus. Less is known, however, about infection and vaccination rates in the different populations that make up the Asian American, Native Hawaiian, and Pacific Islander (AA\/NH\/PI) communities. In at least 16 states that do disaggregate their data, Native Hawaiians and Pacific Islanders have the highest mortality rates. Additionally, reports of incidents of xenophobia and violence against AANHPI community members, particularly women, became more frequent during the pandemic. Finally, there is a lack of data on AANHPI health and well-being in comparison to other groups, which will make it more difficult to correct these disparities in the future. The National Academies of Sciences, Engineering, and Medicine's Roundtable on the Promotion of Health Equity planned and hosted a 2-day public workshop in December 2021 titled COVID-19, Health Equity, and the Asian American, Pacific Islander, and Native Hawaiian Communities. The workshop focused on the impact of the COVID-19 pandemic and the unique obstacles faced by the AANHPI communities in achieving health equity. This Proceedings of a Workshop-In Brief summarizes the events covered in the workshop discussions.

Policing to Promote the Rule of Law and Protect the Population: An Evidence-Based Approach - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The U.S. Department of State, through its Bureau of International Narcotics and Law Enforcement Affairs (INL), provides foreign assistance and supports capacity building for criminal justice systems and police organizations in approximately 90 countries around the world. It has a mandate to strengthen fragile states, support democratic transitions, and stabilize conflict-affected societies by helping partner countries develop effective and accountable criminal justice sector institutions and systems. While the science of policing outcomes has grown in recent years, it is limited in context, with much of the research conducted on policing taking place in the Global North countries (e.g., the United Kingdom and United States). It is also limited in purpose, with much research focused on examining crime reduction as opposed to examining the harms to the public as the result of crimes, violence, and any effects of policing activities. At the request of INL, Policing to Promote the Rule of Law and Protect the Population explores the organizational policies, structures, or practices (e.g., HR and recruiting, legal authorities, reporting lines, etc.) that will enable a police service to promote the rule of law and protect the population. This report presents an overview of the state of research and highlights promising areas to guide policing reform and interventions.

Flying in the COVID-19 Era: Science-based Risk Assessments and Mitigation Strategies on the Ground and in the Air: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The National Academies of Sciences, Engineering, and Medicine convened a workshop on February 4th and 5th, 2021 to review the issues related to safety of passengers and employees in commercial air transportation, for domestic and international travel, during the COVID-19 pandemic. The workshop explored best practices to assess and mitigate COVID-19 transmission risks experienced during the travel chain, from the departure airport entrance to the destination airport exit. The workshop also identified areas where more research is needed to address gaps in understanding. This publication documents the presentations and discussions held during the workshop, and is presented as a synthesis of the workshop.

Integrating Firearm Injury Prevention into Health Care: Proceedings of a Joint Workshop of the National Academies of Sciences, Engineering, and Medicine; Northwell Health; and PEACE Initiative - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The staggering number of deaths and emergency department visits caused by firearm injuries has only grown with time. Costs associated with firearm related injuries amount to over a billion dollars annually in the United States alone, not including physician charges and postdischarge costs. To address this epidemic, in April of 2022, the National Academies of Sciences, Engineering, and Medicine's Board on Population Health and Public Health Practice, in collaboration with Northwell Heath and the PEACE Initiative, brought together firearm injury prevention thought leaders to explore how health systems can integrate interventions for firearm injury prevention into routine care for the purpose of improving the health of patients and communities. The workshop speakers discussed strategies for firearm injury and mortality prevention and its integration into routine care. Speakers also explored facilitators and barriers to implementation strategies, and how health systems might work to overcome those barriers.

Transforming Human Health: Celebrating 50 Years of Discovery and Progress - National Academy of Medicine
The past half-century has been an era of astonishing progress for biomedical science, health, and health care in the United States and worldwide. This volume, commissioned to mark the occasion of the 50th anniversary of the founding of the U.S. National Academy of Medicine (NAM; formerly the Institute of Medicine [IOM]), tells the story of that progress across five major fields: biomedical science and technology, diseases and conditions, public health, U.S. health care, and global health. Since the NAM was founded in 1970, the nation and the world have seen multitudes of remarkable \

Measuring Sex, Gender Identity, and Sexual Orientation - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Sex, gender identity, and sexual orientation are key indicators of the demographic diversity in the United States. Sex and gender are often conflated under the assumptions that they are mutually determined and do not differ from each other; however, the growing visibility of transgender and intersex populations, as well as efforts to improve the measurement of sex and gender across many scientific fields, has demonstrated the need to reconsider how sex, gender, and the relationship between them are conceptualized. This is turn affects sexual orientation, because it is defined on the basis of the relationship between a person's own sex or gender and that of their actual or preferred partners. Sex, gender, and sexual orientation are core aspects of identity that shape opportunities, experiences with discrimination, and outcomes through the life course; therefore, it is crucial that measures of these concepts accurately capture their complexity. Recognition of the diversity within the lesbian, gay, bisexual, transgender, queer, intersex, and other sexual and gender minorities - the LGBTQI+ population - has also led to a reexamination of how the concepts of sex, gender identity, and sexual orientation are measured. Better measurement will improve the ability to identify sexual and gender minority populations and understand the challenges they face. LGBTQI+ people continue to experience disparate and inequitable treatment, including harassment, discrimination, and violence, which in turn affects outcomes in many areas of everyday life, including health and access to health care services, economic and educational attainment, and family and social support. Though knowledge of these disparities has increased significantly over the past decade, glaring gaps remain, often driven by a lack of reliable data. Measuring Sex, Gender Identity, and Sexual Orientation recommends that the National Institutes of Health (NIH) adopt new practices for collecting data on sex, gender, and sexual orientation - including collecting gender data by default, and not conflating gender with sex as a biological variable. The report recommends standardized language to be used in survey questions that ask about a respondent's sex, gender identity, and sexual orientation. Better measurements will improve data quality, as well as the NIH's ability to identify LGBTQI+ populations and understand the challenges they face.

Federal Funding Flexibility: Use of Federal-Aid Highway Fund Transfers by State DOTs - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The Federal-Aid Highway Program (FAHP) represents one of the largest grant programs in the federal domestic budget and is a combination of individual categorical and discretionary grant programs.The TRB National Cooperative Highway Research Program's NCHRP Research Report 1023: Federal Funding Flexibility: Use of Federal-Aid Highway Fund Transfers by State DOTs investigates recent experience with statutory features that allow recipients of formula grants to shift the authority to use federal funds from one FAHP category to another, and even into other modes.Supplemental to the report are a related webinar video, slides from the webinar, and notes from the webinar.

Community Interventions to Prevent Veteran Suicide: The Role of Social Determinants: Proceedings of a Virtual Symposium - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
On March 28 and 29, 2022, the Board on Behavioral, Cognitive, and Sensory Sciences at the National Academies of Sciences, Engineering, and Medicine held a virtual symposium entitled Community Interventions to Prevent Veteran Suicide: The Role of Social Determinants to gain a better understanding of social determinants influencing the recent increase in suicide risk and how currently available practice guidelines can inform community-level preventive interventions, particularly those targeting veteran populations. Presenters and participants explored the relevant social, cultural, and economic factors driving changes in suicide risk among veterans and ways that current best practices for suicide prevention and treatment can be applied at the community level. This publication summarizes the presentations and discussion of the symposium.

Action Collaborative on Preventing Sexual Harassment in Higher Education: Year Three Annual Report of Activities - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The Action Collaborative on Preventing Sexual Harassment in Higher Education is an initiative where over 55 colleges, universities, and other research and training organizations are identifying, researching, developing, and implementing efforts that move beyond basic legal compliance to evidence-based policies and practices for addressing and preventing all forms of sexual harassment and promoting a campus climate of civility and respect. The Partner Network of the Action Collaborative provides an additional opportunity for collective sharing across colleges and universities, research entities, higher education associations, grassroots and non-profit organizations, federal agencies, national laboratories, industry, and other stakeholder organizations. This annual report for 2021-2022 highlights the overall progress of the Action Collaborative toward its goals and summarizes the work shared by member and partner network organizations during the third year of the collaborative.

Global Food Security and Sustainability Implications of the Ukraine Conflict: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
On June 1, 2022, the National Academies of Sciences, Engineering, and Medicine convened a public workshop to discuss global food security challenges arising from the Ukraine conflict and possible approaches to address these challenges. The workshop focused on short-term responses to the current crisis, opportunities for international collaborations, and how the crisis could impact U.S. national security interests in a changing climate, including the relationships between agricultural production, climate change, and security. Discussions also addressed connections among areas such as agricultural production, land use, energy, water, health, and biodiversity critical to promoting long term sustainability. This publication highlights the presentations and discussion of the workshop.

Community Power in Population Health Improvement: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine
To explore issues related to community-driven power-building efforts to improve population health, the Roundtable on Population Health Improvement of the National Academies of Sciences, Engineering, and Medicine hosted a virtual public workshop, \

Reducing Inequalities Between Lesbian, Gay, Bisexual, Transgender, and Queer Adolescents and Cisgender, Heterosexual Adolescents: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
To better understand the inequalities facing lesbian, gay, bisexual, transgender, and queer (LGBTQ) youth and the promising interventions being used to address these inequalities, the National Academies of Sciences, Engineering, and Medicine's Board on Children, Youth, and Families hosted a virtual public workshop titled Reducing Inequalities Between LGBTQ Adolescents and Cisgender, Heterosexual Adolescents, which convened on August 25201327, 2021. The workshop was developed by a planning committee composed of experts from the fields of sociology, medicine, public health, psychology, social work, policy, and direct-service provision. This Proceedings of a Workshop summarizes the presentations and discussions from that workshop.

Models for Population Health Improvement by Health Care Systems and Partners: Tensions and Promise on the Path Upstream: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The Roundtable on Population Health Improvement of the National Academies of Sciences, Engineering, and Medicine hosted a public workshop on September 19, 2019 titled Models for Population Health Improvement by Health Care Systems and Partners: Tensions and Promise on the Path Upstream. The term upstream refers to the higher levels of action to improve health. Medical services act downstream (i.e., at the patient level) in improving population health, while such activities as screening and referring to social and human services (e.g., for housing, food assistance) are situated midstream, and the work of changing laws, policies, and regulations (e.g., toward affordable housing, expanding healthy food access) to improve the community conditions for health represents upstream action. The workshop explored the growing attention on population health, from health care delivery and health insurance organizations to the social determinants of health and their individual-level manifestation as health-related social needs, such as patients' needs. The workshop showcased collaborative population health improvement efforts, each of which included one or more health systems. This publication summarizes the presentations and discussions from the workshop.

Methadone Treatment for Opioid Use Disorder: Improving Access Through Regulatory and Legal Change: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine
Methadone is a Food and Drug Administration- (FDA-) approved medication for treating opioid use disorder (OUD), a chronic brain disease that affects more than 2.7 million people in the United States aged 12 and older. Despite its effectiveness in saving lives, many barriers impede access to, initiation of, and retention in methadone treatment for OUD. To address these barriers, on March 3 and 4, 2022, the National Academies of Sciences, Engineering, and Medicine hosted a workshop on \

Location Data in the Context of Public Health, Research, and Law Enforcement: An Exploration of Governance Frameworks: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
On June 8-9, 2022, an ad hoc planning committee under the auspices of the National Academies of Sciences, Engineering, and Medicine's Committee on Science, Technology, and Law hosted a workshop, Location Data in the Context of Public Health, Research, and Law Enforcement: An Exploration of Governance Frameworks. The workshop examined the collection, interpretation, and use of location data by government, academia, and industry. This publication summarizes the presentations and discussion of the workshop.

Committee on Human Rights: Year in Review 2021 - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
The annual report of the Committee on Human Rights (CHR) provides an overview of the CHR's activities in 2021, including information on its advocacy, events, and awareness-raising projects.

Measurement and Analysis of Public Opinion: An Analytic Framework - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Intelligence analysts conduct these analyses every day, using decades of propriety tradecraft techniques and an arsenal of clandestine information gathering sources, but the resources available are not unlimited. Open source public opinion tools can provide timely and relatively inexpensive methods of understanding fast-moving conditions, acting as a force multiplier to help policymakers have a truly all-source understanding of complex events. By providing analysts with the best practices in survey methodology and nonsurvey methods for gathering data on public opinion, they will be armed with a clearer sense of important shifts in attitudes, elections, and unrest. In order to provide guidance to analysts on strategies for assessing public opinion, representatives from the intelligence community approached the National Academies of Sciences, Engineering, and Medicine to request preparation of a framework on Measuring and Analyzing Public Opinion. This analytic framework includes three layers of information. Layer 1 comprises four authored papers that review literature from various disciplines containing overview information as well as how the topic\/situation of interest can enable better analysis across different situational constraints. Layer 2 is a distilled layer of information in the form of an authored summary of the four Layer 1 papers, both summarizing and describing key points. Finally, Layer 3 provides an even further distillation of the key concepts, in a one-page visual graphic, that displays key drivers from the work in Layers 1 and 2 to help the intended audience apply knowledge to the situation of interest.

Research and Data Priorities for Improving Economic and Social Mobility: Proceedings of a Workshop - National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2022)
Since around 1980, fewer Americans than before are doing better than their parents had 2013 that is, more are experiencing downward social and economic mobility in terms of occupational status and income. This trend in downward mobility is occurring amidst high and rising levels of inequality in income, wealth, health, and life expectancy. To better understand the factors that influence social and economic mobility, the Committee on Population and the Committee on National Statistics hosted a workshop on February 14-15, 2022. The proceedings from this workshop identify key priorities for future research and data collection to improve social and economic mobility.